Calpain inhibition rescues troponin T3 fragmentation, increases Cav1.1, and enhances skeletal muscle force in aging sedentary mice - Zhang, Tan (2016)
Loss of strength in human and animal models of aging can be partially attributed to a well-recognized decrease in muscle mass; however, starting at middle-age, the normalized force (force/muscle cross-sectional area) in the knee extensors and single muscle fibers declines in a curvilinear manner. Strength is lost faster than muscle mass and is a more consistent risk factor for disability and death. Reduced expression of the voltage sensor Ca2+ channel α1 subunit (Cav1.1) with aging leads to excitation-contraction uncoupling, which accounts for a significant fraction of the decrease in skeletal muscle function. We recently reported that in addition to its classical cytoplasmic location, fast skeletal muscle troponin T3 (TnT3) is fragmented in aging mice, and both full-length TnT3 (FL-TnT3) and its carboxyl-terminal (CT-TnT3) fragment shuttle to the nucleus. Here, we demonstrate that it regulates transcription of Cacna1s, the gene encoding Cav1.1. Knocking down TnT3 in vivo downregulated Cav1.1. TnT3 downregulation or overexpression decreased or increased, respectively, Cacna1s promoter activity, and the effect was ablated by truncating the TnT3 nuclear localization sequence. Further, we mapped the Cacna1s promoter region and established the consensus sequence for TnT3 binding to Cacna1s promoter. Systemic administration of BDA-410, a specific calpain inhibitor, prevented TnT3 fragmentation, and Cacna1s and Cav1.1 downregulation and improved muscle force generation in sedentary old mice.